The synthesis of diverse benzazepinoindoles via gold-catalyzed post-Ugi alkyne hydroarylation/Michael addition sequence - Chao Liu; Luc Van Meervelt; Vsevolod A. Peshkov; Erik V. Van der Eycken (Royal Society of Chemistry (RSC), 2022)
We have developed a novel gold-catalyzed hydroarylation/Michael addition process, enabling the con struction of the benzazepinoindole polycyclic scaffold in a highly efficient manner starting from readily accessible multifunctional Ugi adducts. The developed methodology is characterized by a broad substrate scope, excellent functional-group tolerance and high yields of the target benzazepinoindoles.
Keywords: Alkyne; Catalysis; Combinatorial chemistry; Organic chemistry; type of access: open access